The effects of special displays on shopping behavior. (March 2015) - Wang, Shih-Ching; Lang, Mark
Abstract: This study examined the unintended effects and consequences of special displays on subsequent shopping behavior. Special displays are studied as a prominent form of in-store or shopper marketing activity. Two experiments are performed using special value and natural food displays in an online simulated store environment. The impact of exposure to special displays on mind-sets and resulting product choices are tested in a shopping task. Impact on store image is also tested. A total of 896 respondents were recruited in this study. The results showed that special displays did trigger specific mind-sets that affected product choices and store image. Special value displays heightened store low-price image without lowering the high-quality image, and triggered a value-oriented mindset, among low price-conscious individuals, that made them place greater weight on price during the ensuing shopping trip. Special natural food display improved store high-quality image without decreasing the low-price image, and triggered a non-value-oriented mindset, among high price-conscious individuals, that made them place lesser weight on price during the remainder of the shopping trip. Findings suggested retailers to consider the total effects and consequences of special displays when designing and executing in-store marketing activity. Highlights: This study examines the unplanned effects of special displays on shopping behavior. Special displays trigger some mind-sets that affect product choices and store image. The level of price consciousness moderates the main effects of special displays. Social influence does not moderate the main effects of special displays.